The 84-bp Indel Polymorphism of The Sterol Regulatory Element-Binding Protein 1 (SREBP1) Gene in Several Cattle Breeds in Indonesia - Saiful Anwar; Widya Pintaka Bayu Putra; Isyana Khaerunnisa; Ari Sulistyo Wulandari; Koko Wisnu Prihatin; Sutikno Sutikno (Indonesian Center for Animal Research and Development (ICARD), 2023)
Sterol regulatory element-binding protein 1 (SREBP1) gene is a gene that encodes SREBP1, a family of transcription factors that have a key role in lipid homeostasis as well as fatty acid metabolisms. The present study aimed to detect the 84-bp indel polymorphism in the intron 5 of the SREBP1 gene (84-bp indel) in several cattle breeds in Indonesia. A total of 740 cattle of six breeds (Limousin, Simmental, Holstein-Friesian, Bali, Sumbawa, and Pasundan) from two National Artificial Insemination Centers (NAICs) and smallholder farmers were used in this study. The detection of 84-bp indel polymorphism was performed using the polymerase chain reaction (PCR) method and visualized through a gel agarose electrophoresis system. The study showed that the L allele (insertion-type) was common and is fixed in Holstein-Friesian, Bali, and Sumbawa cattle (1.00). Meanwhile, the S allele (deletion-type) was found in Limousin, Simmental, and Pasundan cattle with a frequency of 0.24, 0.16, and 0.01, respectively. The presence of the S allele in Pasundan cattle was only found in the form of the heterozygous LS genotype (0.03). In conclusion, the 84-bp indel of the SREBP1 gene was found to be polymorphic in Limousin, Simmental, and Pasundan cattle, but monomorphic in Holstein-Friesian, Bali, and Sumbawa cattle.